Prosocial behavior and youth mental health outcomes: A scoping review protocol. - Saima Hirani; Emmanuela Ojukwu; Nilanga Aki Bandara (PLoS ONE)
Introduction This review aims to explore the existing literature about the virtue of helping others and its association with youth mental health. Mental health of youth is rooted in their social environment. Helping others or engaging in prosocial behavior are activities that youth may participate in. The notion of helping others and its association with individual mental well-being have been well-studied for adults and older adults and to some extent in youth, however, no review has been conducted to understand the intersection of helping others and mental health in the youth population. Methods This review will consider all study designs that examine helping others and mental health of youth. The inclusion criteria for the review will include young individuals aged 10-24-year-old, living in any geographic location, of all gender identities, and with or without mental health issues. Grey literature and studies that only speak to outcomes related to physical well-being will be excluded. A search will be conducted in CINAHL, MEDLINE and PsycINFO. Studies published in the English language will be included with no restriction on publication time period. Articles will be screened against the inclusion criteria onto a single software by two independent reviewers. In the case of any disagreement, a third independent reviewer would resolve the conflict. Findings Data will be extracted and presented in a tabular or diagrammatic form supported by a summary. We will report our findings in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for Scoping Reviews (PRISMA-ScR). The findings of this review will provide evidence-based recommendations for promoting youth mental health and a basis for future research.